2023
DOI: 10.3389/fnint.2023.1052683
|View full text |Cite
|
Sign up to set email alerts
|

Care patterns and Traditional Chinese Medicine constitution as factors of depression and anxiety in patients with systemic sclerosis: A cross-sectional study during the COVID-19 pandemic

Abstract: ObjectiveCare patterns and Traditional Chinese Medicine (TCM) constitution affects the emotion and health of patients with systemic sclerosis (SSc) while the prevalence of COVID-19 may aggravate such patients’ emotion and health. We investigated the depression and anxiety levels of patients with SSc during the pandemic to identify the correlation between care patterns, TCM constitution, and patients’ emotion.Materials and methodsThis was a cross-sectional study. Patients with SSc and healthy individuals were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…For example, a systematic evaluation study of TCMC as a predictor of depression showed that Qi-deficiency constitution and Qi-depression constitution could be used as a predictor of depression [ 43 ]. A cross-sectional study during the COVID-19 pandemic showed that Qi-deficiency constitution and Qi-depression constitution were associated with depression and Qi-depression constitution was associated with anxiety in patients with systemic sclerosis [ 44 ]. A study of Malaysian university students also showed that Qi-depression constitution was an important risk factor for depression among university students [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a systematic evaluation study of TCMC as a predictor of depression showed that Qi-deficiency constitution and Qi-depression constitution could be used as a predictor of depression [ 43 ]. A cross-sectional study during the COVID-19 pandemic showed that Qi-deficiency constitution and Qi-depression constitution were associated with depression and Qi-depression constitution was associated with anxiety in patients with systemic sclerosis [ 44 ]. A study of Malaysian university students also showed that Qi-depression constitution was an important risk factor for depression among university students [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that TCM constitution is closely related to the occurrence, development and prognosis of diseases. [7][8][9][10][11][12]22 Therefore, a balanced TCM constitution has important potential application value in preventing and alleviating clinical symptoms of COVID-19 patients and accelerating the negative nucleic acid transformation of COVID-19 patients. The time taken for COVID-19 nucleic acid conversion is related to sex, age, vaccination status, 1-3 BMI, 2 chronic diseases, 24,25 presence of sore throat symptoms, 4 high nutrition risk 26 and plasma 25(OH)D levels.…”
Section: Discussionmentioning
confidence: 99%
“…TCM constitution differences determine the susceptibility to certain diseases and the prognosis of the diseases. [7][8][9][10][11][12] Traditional Chinese medicine constitution theory believes that through diet, exercise, 28 drug conditioning and other methods can improve people's unbalanced constitution, so as to prevent the occurrence of disease, or improve the condition of patients who have been sick, and promote the recovery of disease. 29,30 Therefore, the TCM constitution has enormous potential for disease prevention and treatment applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation